Drug Release Profile and Cellular Uptake of Polymeric Prodrugs Synthesized from Amphiphilic Blockcopolymer Using Mechanically Produced Macromonomers Possessing Anhydrate as a Terminal Group - Shin-ichi Kondo; Sayaka Kimura; Kenjiro Tatematsu; Yuka Sawama; Naoki Doi; Yasushi Sasai; Yukinori Yamauchi; Masayuki Kuzuya (Journal of Pharmacy and Nutrition Sciences, 2016)
In this paper, the polymeric micelle was fabricated with amphiphilic block copolymer which was synthesized by the condensation of mechanochemically produced PBzMA macromonomer with a-methyl-w-aminopropoxy polyoxyethylene. Although the polymeric micelles containing 5-fluorouracil (5-FU) or rohdamine showed the narrow size distribution as well as blank polymeric micelles, the particle diameter of the polymeric micelles containing 5-FU or rohdamine was larger than that of blank polymeric micelle. Polymeric micelle containing 5-FU slowly released 5-FU and about 10 % of 5-FU was released within 72 h. The present polymeric micelle was uptaken by A549 cells, but HepG2 cells did not. Cytotoxicity of Polymeric micelle containing 5-FU was not observed against HepG2 and A549 cells in this experimental condition. It was considered that the slow release of 5-FU from Polymeric micelle might cause the insufficient cytotoxicity.